A method for preparing PA10T transparent nylon by in-situ copolymerization and its application

CN122940997APending Publication Date: 2026-10-20SHANDONG XIANGLONG NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611424004.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]本申请实施的目的在于提供一种原位共聚法制备PA10T透明尼龙的方法及应用,以解决现有技术中存在的PA10T尼龙透明度低,性能差(尤其是耐高温特性和吸水性),制备必须在高温高压下才能完成聚合反应过程的技术问题

Benefits of technology

1、本方法采用“升温升压预聚-升温保压反应-升温升压初聚-升温降压聚合-常压氮吹去除小分子”五步原位共聚策略,逐步推进聚合反应进程,220 ℃、20 kg压力下预聚1.5-2 h,有助于单体盐充分反应生成低聚物,避免爆聚;S2阶段在保持压力下升温至260℃,促进链增长;S3阶段进一步提升压力至30-31 kg,增强反应体系活性,加速聚合;S4阶段缓慢降压至常压并升温至280 ℃,有效调控聚合速率与分子量分布,防止局部过热或降解;S5阶段通氮气去除残留小分子及低聚物,显著改善后续拉条切粒效果,避免断条、气泡等问题,提高产品颗粒均匀性与加工稳定性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This application discloses a method for preparing PA10T transparent nylon by in-situ copolymerization and its application. Belonging to the field of nylon preparation technology, the method uses PA10T and phthalic acid monomer salt as the main components, and involves in-situ copolymerization through a single-stage process consisting of five stages: heating and pressurizing, heating and holding, heating and pressurizing again, heating and depressurizing, and nitrogen blowing at atmospheric pressure. The material is then discharged under pressure, stretched, cooled, and pelletized to prepare PA10T transparent nylon. The obtained PA10T transparent nylon exhibits good high-temperature thermal stability, lower water absorption for better dimensional stability during post-processing, and improved mechanical properties, thus expanding the application industries and fields of transparent nylon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of nylon preparation technology, and in particular relates to a method for preparing PA10T transparent nylon by in-situ copolymerization and its application. Background Technology

[0002] Nylon possesses excellent mechanical properties, heat resistance, dimensional stability, chemical corrosion resistance, hydrolysis resistance, and good processing performance, along with low water absorption. It is widely used in automotive, machinery, aerospace, electronics, and medical and health fields. Modified transparent nylon exhibits improved performance and an even wider range of applications. Research findings and products on transparent nylon are numerous. Existing reports and research primarily focus on PA6T, a semi-aromatic high-temperature resistant transparent nylon, with less research on PA10T. However, some research data indicates that PA10T has the best overall performance among semi-aromatic high-temperature resistant nylons.

[0003] PA10T belongs to the category of bio-based nylon. Since the monomer decanediamine used to synthesize PA10T comes from castor oil, which is a green and renewable resource, PA10T has high environmental value. It is also the only bio-based semi-aromatic polyamide synthesized so far, making it an environmentally friendly product and very meaningful for sustainable development.

[0004] However, only a handful of companies in China can produce PA10T. Research and development of PA10T transparent nylon has largely remained in the laboratory. CN115594840A introduces isosorbide with diamine, diacid, and aromatic acid to copolymerize, obtaining bio-based transparent nylon; CN105330845A introduces polyurethane amide with diamine diacid to copolymerize, obtaining bio-based transparent nylon; CN1041957A, this type of polyamide, is prepared by reacting lactam or amino acid compounds with terephthalic acid or a mixture of terephthalic acid and isophthalic acid in the first step, and then reacting the resulting diacid oligomer with a cyclic aliphatic diamine in the second step. While these three patented copolymer formulations achieve the properties of transparent nylon, the presence of multiple heterochains compromises its superior low water absorption and reduces inherent properties such as high-temperature resistance. Current technologies do not clearly define the discharge after polymerization, whether it can be stretched and granulated, leaving gaps in the preparation process. Whether the results can be immediately industrialized remains uncertain. Summary of the Invention

[0005] The purpose of this application is to provide a method and application for preparing PA10T transparent nylon by in-situ copolymerization, so as to solve the technical problems of low transparency and poor performance (especially high temperature resistance and water absorption) of PA10T nylon in the prior art, and the fact that the polymerization reaction process can only be completed under high temperature and high pressure.

[0006] To achieve the above objectives, the technical solution adopted in this application is: to provide a PA10T transparent nylon, comprising PA10T monomer salt, phthalic acid monomer salt, auxiliary catalyst, antioxidant and molecular weight regulator.

[0007] In one embodiment, The PA10T monomer salt comprises decanediamine and terephthalic acid, wherein the molar ratio of decanediamine to terephthalic acid is 1:1.

[0008] In one embodiment, The phthalic acid monomer salt comprises phthalic acid and an alicyclic amine, wherein the molar ratio of phthalic acid to the alicyclic amine is 1:1; The phthalic acid is terephthalic acid or isophthalic acid, and the alicyclic amine is one of MACM, HMDA, decanediamine or hexamethylenediamine; The mass ratio of PA10T monomer salt to phthalic acid monomer salt is 6-8.5 : 1.5-4.

[0009] In one embodiment, The auxiliary catalyst is one of phosphoric acid, p-toluenesulfonic acid, zinc acetate, sodium hypophosphite, or calcium hypophosphite, and the amount of the auxiliary catalyst added is 0.01-0.1% of the total amount of PA10T monomer salt and phthalic acid monomer salt.

[0010] In one embodiment, The antioxidant is one or two of SEED, 1098, 168, 1010, H10 or 626, and the amount of the antioxidant added is 0.01-0.1% of the total amount of PA10T monomer salt and phthalic acid monomer salt.

[0011] In one embodiment, The molecular weight regulator is one of glacial acetic acid, adipic acid, or benzoic acid, and the amount of the molecular weight regulator added is 0.03-1.5% of the total amount of PA10T monomer salt and phthalic acid monomer salt.

[0012] This application also provides a method for preparing PA10T transparent nylon by in-situ copolymerization, which specifically includes the following steps: (I) Preparation of PA10T monomer salt: Add decanediamine and terephthalic acid to pure water and heat to neutralize to prepare PA10T monomer salt; (II) Preparation of copolymer salt solution: The phthalic acid monomer salt is heated and mixed with the PA10T monomer salt. Then, an auxiliary catalyst, antioxidant and molecular weight regulator are added and mixed to obtain the copolymer salt solution. (III) In-situ copolymerization: The copolymer salt is pumped into the reactor, and the following steps are completed in sequence; S1, Prepolymerization stage with increased temperature and pressure: Temperature 220 ℃, pressure 20 kg, reaction time 1.5-2 h; S2, Temperature and Pressure Holding Reaction Stage: Pressure 20 kg, temperature raised to 260 ℃, reaction for 1-2 h; S3, Initial polymerization stage with increased temperature and pressure: Increase temperature to 275 ℃, pressure to 30-31 kg, react for 20 min, and adjust the exhaust valve to maintain the pressure. S4. Heating and depressurization polymerization stage: Heat to 280 ℃, depressurize to zero, polymer temperature 292 ℃, react for 1-2 h; S5. Atmospheric pressure nitrogen blowing: Purge with nitrogen for 10-15 min until the polymer temperature reaches 295 ℃, then stop the stirrer; pressurize to balance, stretch, cool, and pelletize to obtain PA10T transparent nylon chips.

[0013] In one embodiment, The heating temperature in step (i) is 85-125 ℃; the heating temperature in step (ii) is 85-90 ℃.

[0014] In one embodiment, The depressurization rate in step S4 is 1 kg / 3 min, and the specific steps for pressurization and balancing in step S5 are: pressurize nitrogen to 5 kg and balance for 5-15 min.

[0015] This application also provides an application of PA10T transparent nylon, which can be used in the automotive industry, electronics, drinking water and water treatment, medical equipment and aerospace fields.

[0016] This application provides a method for preparing PA10T transparent nylon via in-situ copolymerization and its application. Through a precisely designed five-stage polymerization process, the efficient and controllable synthesis of PA10T transparent nylon is achieved, significantly improving the material's transparency, mechanical properties, and processing stability. Compared with existing technologies, it has the following advantages: 1. This method employs a five-step in-situ copolymerization strategy: "prepolymerization with increased temperature and pressure - reaction with increased temperature and pressure - initial polymerization with increased temperature and pressure - polymerization with increased temperature and pressure - removal of small molecules by nitrogen blowing at atmospheric pressure." This strategy progressively advances the polymerization reaction. Prepolymerization at 220 °C and 20 kg pressure for 1.5-2 h helps the monomer salt react fully to generate oligomers and avoids explosive polymerization. In stage S2, the temperature is increased to 260 °C while maintaining pressure to promote chain growth. In stage S3, the pressure is further increased to 30-31 kg to enhance the activity of the reaction system and accelerate polymerization. In stage S4, the pressure is slowly reduced to atmospheric pressure and the temperature is increased to 280 °C to effectively control the polymerization rate and molecular weight distribution, preventing local overheating or degradation. In stage S5, nitrogen is purged to remove residual small molecules and oligomers, significantly improving the subsequent pelletizing effect, avoiding problems such as pellet breakage and bubbles, and improving the uniformity and processing stability of the product particles. 2. By controlling the temperature and pressure in stage S4 and purifying with nitrogen blowing in stage S5, the number of bubbles, micropores, and low-molecular-weight residues inside the polymer is effectively reduced, and the light scattering center is lowered. The light transmittance of the prepared PA10T transparent nylon reaches 86.6-90.4%, which is much higher than that of conventional PA10T materials. This significantly improves the light transmittance and appearance quality of transparent nylon, meeting the needs of high-transparency applications. The water absorption rate of the PA10T transparent nylon prepared by this method is only 0.24-0.34%, which is significantly lower than that of traditional transparent nylon materials. This indicates that in-situ copolymerization effectively retains the low water absorption advantage of PA10T, while also exhibiting good heat resistance and comprehensive mechanical properties, making it suitable for high-temperature and high-humidity environments such as automobiles and electronic appliances.

[0017] 3. Existing technologies generally lack clear post-polymerization discharge and pelletizing processes, making it difficult to achieve continuous industrial production of products. This application designs a pressure-balanced combination of strip cooling pelletizing, which realizes a stable and continuous pelletizing process, overcomes the problem of high-viscosity melts being difficult to stretch, solves the post-processing difficulties and industrialization bottlenecks in existing technologies, and provides a feasible path for the industrial production of PA10T transparent nylon. 4. This method uses bio-based decanediamine as raw material. No additional organic solvents are required during the in-situ copolymerization process. The only byproduct is water. Nitrogen blowing further reduces the emission of small molecules. The overall process is environmentally friendly and meets the requirements of green chemical industry and sustainable development. Detailed Implementation

[0018] To make the technical problems, technical solutions, and beneficial effects to be solved by this application clearer, this application will be further described in detail. It should be understood that the specific embodiments described herein are only for explaining this application and are not intended to limit this application.

[0019] Example 1 A method for preparing PA10T transparent nylon by in-situ copolymerization specifically includes the following steps: (I) Preparation of PA10T monomer salt: Add 5000 g of high-purity water to the neutralization salt formation tank, start the stirrer, heat the high-purity water to 90 ℃, and slowly add 3500 g of PA10T monomer salt prepared by mixing decanediamine and terephthalic acid at a molar ratio of 1:1 into the high-purity water. (II) Preparation of copolymer salt solution: Under the condition of 85-90 ℃, prepare 1500 g of MACMT monomer salt (the mass ratio of PA10T monomer salt to MACMT monomer salt is 7:3) by mixing MACM and terephthalic acid at a molar ratio of 1:1. Then slowly add it to PA10T monomer salt; then add 25 g of benzoic acid, 15 g of 1098, 10 g of H10 and 2 g of sodium hypophosphite and mix to obtain copolymer salt solution; (III) In-situ copolymerization: The copolymer salt is pressed into the reactor using nitrogen gas, the stirrer is started, and the following steps are completed in sequence; S1, Prepolymerization stage with increased temperature and pressure: temperature 220 ℃, pressure 20 kg, reaction time 1.8 h; S2, Heating and Pressure Holding Reaction Stage: Heat to 260 ℃, open the exhaust valve, adjust the valve to maintain a pressure of 20 kg, and react for 1-2 h; S3, Initial polymerization stage of heating and pressurization: After holding the pressure for 1 hour, heat up to 275 ℃, slowly increase the pressure to 30-31 kg, and adjust the exhaust valve to maintain for 20 minutes; S4. Heating and depressurization polymerization stage: As moisture is continuously removed, the temperature of the melt in the reactor gradually rises. When the temperature reaches 280℃, the pressure is reduced to zero at a rate of 1 kg / 3 min. This stage is the exothermic stage, which lasts for 1.6 h. At this time, the polymer temperature is 292℃. S5. Stage for removing residual small molecules by nitrogen blowing at atmospheric pressure: Small molecule water and other low-melting-point oligomers still remain and affect the strip pulling and pelletizing effect. Nitrogen gas is blown for 10-15 min to remove residual small molecules. When the polymer temperature is 295 ℃, the stirrer speed is reduced to 30-45 rpm / min and then the stirrer is stopped. Nitrogen gas is pressurized to 5 kg, equilibrated for 5-15 min, strip pulled, cooled and pelletized to obtain 4176 g of PA10T transparent nylon, with a yield of 83.5%.

[0020] Example 2 The difference between this embodiment and Example 1 is that HMDA and terephthalic acid were prepared in a molar ratio of 1:1 to form 1500 g of HMDAT monomer salt, and the mass ratio of PA10T monomer salt to HMDAT monomer salt was 7:3; the amount of benzoic acid added was 25 g; the rest of the operations were the same, and PA10T transparent nylon was obtained.

[0021] Example 3 The difference between this embodiment and Example 1 is that 4000 g of PA10T salt was used, and 1000 g of HMDA and isophthalic acid were prepared by mixing them in a molar ratio of 1:1 to form 1000 g of HMDAI monomer salt. The mass ratio of PA10T monomer salt to HMDAI monomer salt was 8:2. The amount of benzoic acid added was 64 g. The rest of the operations were the same, and PA10T transparent nylon was obtained.

[0022] Example 4 The difference between this embodiment and Example 3 is that MACM and isophthalic acid were prepared in a molar ratio of 1:1 to form 1000 g of MACMI monomer salt, and the mass ratio of PA10T monomer salt to MACMI monomer salt was 8:2; the rest of the operations were the same, and PA10T transparent nylon was obtained.

[0023] Example 5 The difference between this embodiment and Example 1 is that 1050 g of PA10T salt was used, and 3950 g of 10I monomer salt was prepared by mixing decanediamine and isophthalic acid at a molar ratio of 1:1. The mass ratio of PA10T monomer salt to 10I monomer salt was 7:3. 1.5 g of sodium hypophosphite was added, and the amount of benzoic acid added was 27 g, 20 g of 1098, and 10 g of 626. The rest of the operation was the same, and PA10T transparent nylon was obtained.

[0024] Example 6 The difference between this embodiment and Example 1 is that 4000 g of PA10T salt was used, and 1000 g of 6I monomer salt was prepared by mixing hexamethylenediamine and isophthalic acid in a molar ratio of 1:1. The mass ratio of PA10T monomer salt to 6I monomer salt was 8:2. The amount of benzoic acid added was 35 g. The rest of the operation was the same, and PA10T transparent nylon was obtained.

[0025] Example 7 The difference between this embodiment and Example 1 is that 3000 g of PA10T salt and 2000 g of MACMT monomer salt were used, and the mass ratio of PA10T monomer salt to MACMT monomer salt was 6:4. The rest of the operations were the same, and PA10T transparent nylon was obtained.

[0026] Example 8 The difference between this embodiment and Example 1 is that 3750 g of PA10T salt and 1250 g of MACMT monomer salt were used, and the mass ratio of PA10T monomer salt to MACMT monomer salt was 7.5:2.5. The rest of the operations were the same, and PA10T transparent nylon was obtained.

[0027] Example 9 The difference between this embodiment and Example 9 is that 3750 g of PA10T salt and 1250 g of HMDAT monomer salt were used, and the mass ratio of PA10T monomer salt to HMDAT monomer salt was 7.5:2.5. The rest of the operations were the same, and PA10T transparent nylon was obtained.

[0028] Example 10 The difference between this embodiment and Example 1 is that terephthalic acid is replaced with isophthalic acid, PA10T salt 3750 g, MACMI monomer salt 1250 g, and the mass ratio of PA10T monomer salt to MACMI monomer salt is 7.5:2.5. The rest of the operation is the same, and PA10T transparent nylon is obtained.

[0029] Example 11 The difference between this embodiment and Example 11 is that 4250 g of PA10T salt and 750 g of MACMI monomer salt were used, and the mass ratio of PA10T monomer salt to MACMI monomer salt was 8.5:1.5. The rest of the operations were the same, and PA10T transparent nylon was obtained.

[0030] Example 12 The difference between this embodiment and Example 1 is that MACM is replaced with HMDA, terephthalic acid is replaced with isophthalic acid, PA10T salt 3750 g, HMDAI monomer salt 1250 g, the mass ratio of PA10T monomer salt to HMDAI monomer salt is 7.5 : 2.5, the rest of the operation is the same, and PA10T transparent nylon is obtained.

[0031] Example 13 The difference between this embodiment and Example 1 is that MACM is replaced with hexamethylenediamine, terephthalic acid is replaced with isophthalic acid, 3500 g of PA10T salt and 1500 g of 6I monomer salt are used, and the mass ratio of PA10T monomer salt to 6I monomer salt is 7:3. The rest of the operation is the same, and PA10T transparent nylon is obtained.

[0032] Example 14 The difference between this embodiment and Example 1 is that sodium hypophosphite is replaced with phosphoric acid, 1098 is replaced with SEED, H10 is not used, and benzoic acid is replaced with glacial acetic acid. The rest of the operations are the same, and PA10T transparent nylon is obtained.

[0033] Example 15 The difference between this embodiment and Example 1 is that sodium hypophosphite is replaced with p-toluenesulfonic acid, 1098 is replaced with 168, H10 is not used, and benzoic acid is replaced with adipic acid. The remaining operations are the same, and PA10T transparent nylon is obtained.

[0034] Example 16 The difference between this embodiment and Example 1 is that sodium hypophosphite is replaced with zinc acetate, 1098 is replaced with 1010, and H10 is not used. The other operations are the same, and PA10T transparent nylon is obtained.

[0035] Example 17 The difference between this embodiment and Example 1 is that sodium hypophosphite is replaced with calcium hypophosphite, while the rest of the operations are the same, to obtain PA10T transparent nylon.

[0036] Comparative Example 1 A method for preparing PA10T nylon specifically includes the following steps: (I) Preparation of PA10T monomer salt: Add 5000 g of high-purity water to the neutralization salt formation tank, start the stirrer, heat the high-purity water to 90 ℃, and slowly add 3500 g of PA10T monomer salt prepared by mixing decanediamine and terephthalic acid at a molar ratio of 1:1 into the high-purity water. (II) Preparation of copolymer salt solution: Mix MACM and terephthalic acid at a molar ratio of 1:1 to prepare 1500 g of MACMT monomer salt (the mass ratio of PA10T monomer salt to MACMT monomer salt is 7:3) and slowly add it to PA10T monomer salt; then add 25 g of benzoic acid, 15 g of 1098, 10 g of H10 and 2 g of sodium hypophosphite and mix to obtain copolymer salt solution; (III) PA10T nylon is obtained by treating the copolymer salt solution.

[0037] Experimental Example 1 The performance of the nylons prepared in Examples 1-5 and Comparative Example 1 was tested, and the results are shown in Table 1. Table 1. Nylon performance test results

[0038] This application provides a method for preparing PA10T transparent nylon by in-situ copolymerization and its application. Due to the special physicochemical properties of PA10T material and the requirements of the production process, and because the copolymer components are all long-chain rigid benzene ring nylon salts, although the melting temperature is reduced, PA10T transparent nylon not only has wear resistance and barrier properties that are even better than those of similar transparent nylons, but also has good high-temperature thermal stability compared with other semi-aromatic nylons such as PA6T high-temperature transparent nylon. The lower water absorption rate makes the dimensional stability of post-processing better, and the mechanical properties are better, thus expanding the application industries and fields of transparent nylon.

[0039] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A PA10T transparent nylon, characterized in that, It includes PA10T monomer salt, phthalic acid monomer salt, auxiliary catalyst, antioxidant and molecular weight regulator.

2. The PA10T transparent nylon according to claim 1, characterized in that, The PA10T monomer salt comprises decanediamine and terephthalic acid, wherein the molar ratio of decanediamine to terephthalic acid is 1:

1.

3. The PA10T transparent nylon according to claim 1, characterized in that, The phthalic acid monomer salt comprises phthalic acid and an alicyclic amine, wherein the molar ratio of phthalic acid to the alicyclic amine is 1:1; The phthalic acid is terephthalic acid or isophthalic acid, and the alicyclic amine is one of MACM, HMDA, decanediamine or hexamethylenediamine; The mass ratio of PA10T monomer salt to phthalic acid monomer salt is 6-8.5 : 1.5-4.

4. The PA10T transparent nylon according to claim 1, characterized in that, The auxiliary catalyst is one of phosphoric acid, p-toluenesulfonic acid, zinc acetate, sodium hypophosphite, or calcium hypophosphite, and the amount of the auxiliary catalyst added is 0.01-0.1% of the total amount of PA10T monomer salt and phthalic acid monomer salt.

5. The PA10T transparent nylon according to claim 1, characterized in that, The antioxidant is one or two of SEED, 1098, 168, 1010, H10 or 626, and the amount of the antioxidant added is 0.01-0.1% of the total amount of PA10T monomer salt and phthalic acid monomer salt.

6. The PA10T transparent nylon according to claim 1, characterized in that, The molecular weight regulator is one of glacial acetic acid, adipic acid, or benzoic acid, and the amount of the molecular weight regulator added is 0.03-1.5% of the total amount of PA10T monomer salt and phthalic acid monomer salt.

7. A method for preparing PA10T transparent nylon by in-situ copolymerization, characterized in that, Specifically, the following steps are included: (I) Preparation of PA10T monomer salt: Add decanediamine and terephthalic acid to pure water and heat to neutralize to prepare PA10T monomer salt; (II) Preparation of copolymer salt solution: The phthalic acid monomer salt is heated and mixed with the PA10T monomer salt. Then, an auxiliary catalyst, antioxidant and molecular weight regulator are added and mixed to prepare the copolymer salt solution. (III) In-situ copolymerization: The copolymer salt is pumped into the reactor, and the following steps are completed in sequence; S1, Prepolymerization stage with increased temperature and pressure: Temperature 220 ℃, pressure 20 kg, reaction time 1.5-2 h; S2, Temperature and Pressure Holding Reaction Stage: Pressure 20 kg, temperature raised to 260 ℃, reaction for 1-2 h; S3, Initial polymerization stage with increased temperature and pressure: Increase temperature to 275 ℃, pressure to 30-31 kg, react for 20 min, and adjust the exhaust valve to maintain the pressure. S4. Heating and depressurization polymerization stage: Heat to 280 ℃, depressurize to zero, polymer temperature 292 ℃, react for 1-2 h; S5. Atmospheric pressure nitrogen blowing: Purge with nitrogen for 10-15 min until the polymer temperature reaches 295 ℃, then stop the stirrer; pressurize to balance, stretch, cool, and pelletize to obtain PA10T transparent nylon chips.

8. The method for preparing PA10T transparent nylon by in-situ copolymerization according to claim 7, characterized in that, The heating temperature in step (i) is 85-125 ℃; the heating temperature in step (ii) is 85-90 ℃.

9. The method for preparing PA10T transparent nylon by in-situ copolymerization according to claim 7, characterized in that, The depressurization rate in step S4 is 1 kg / 3 min, and the specific steps for pressurization and balancing in step S5 are: pressurize nitrogen to 5 kg and balance for 5-15 min.

10. An application of an in-situ copolymerization method for preparing PA10T transparent nylon, characterized in that, PA10T transparent nylon is used in the automotive industry, electronics, drinking water and water treatment, medical equipment and aerospace.

Citation Information

Patent Citations

  • Transparent polyamides, process for their manufacture

    CN1041957A

  • Bio-based transparent nylon and synthesis method thereof

    CN105330845A

  • Bio-based copolymerized transparent nylon and preparation method thereof

    CN115594840A